Homogenizing process of lithium ion battery silicon-carbon negative electrode slurry and negative electrode slurry
By controlling the solid content and temperature and adding components in stages, the problem of increased bubbles and viscosity in lithium battery silicon-carbon anode slurry during standing or slow stirring was solved, thus improving the stability of the slurry and the surface quality of the electrode.
Patent Information
- Application Number
- CN202511532754.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-01-20
AI Technical Summary
During long-term standing or slow stirring, the silicon-carbon anode slurry for lithium batteries generates a large number of bubbles, which leads to surface defects and a sharp increase in viscosity in the coated electrode, affecting the electrode processing quality and battery performance.
By controlling the solid content of the slurry between 60-65% and strictly controlling the mixing temperature to not exceed 40℃, single-walled carbon nanotube conductive slurry and polyacrylic acid binder are added in stages to avoid the rapid formation of hydrogen bonds. After initial mixing at a low speed, the dispersion speed is gradually increased to ensure that each component is uniformly dispersed.
It effectively reduces bubble formation, improves slurry stability and coating quality, ensures electrode surface consistency, and enhances battery performance.
Smart Images

Figure CN121366876A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium battery negative electrode slurry preparation, and particularly relates to a lithium ion battery silicon-carbon negative electrode slurry homogenizing process and negative electrode slurry. BACKGROUND
[0002] The statements herein are provided only to further provide context of the present application and are not necessarily prior art.
[0003] The lithium battery silicon-carbon negative electrode slurry glue solution usually takes polyacrylic acid (PAA) as a main binder, and is used in cooperation with styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC). The preparation process is as follows: taking deionized water as a solvent, the CMC is dissolved in the deionized water to form a glue solution; the glue solution is then added into a stirring cylinder in batches in a specific order and mass, and is stirred, and finally the preparation of the negative electrode slurry is completed. During long-term standing or slow stirring, a large amount of bubbles is generated in the negative electrode slurry, which causes surface defects of the coated electrode sheet, and the electrode sheet cannot be normally used. At the same time, the viscosity of the slurry is sharply increased, which affects the consistency of the coating surface density. These problems seriously affect the processing quality of the electrode sheet and the overall performance of the battery. The negative electrode slurry preparation process in the prior art does not optimize the above problems. SUMMARY
[0004] In view of the problems in the prior art, the present application aims to provide a lithium ion battery silicon-carbon negative electrode slurry homogenizing process and negative electrode slurry.
[0005] In order to achieve the above-mentioned purpose, the present application is implemented by the following technical solutions: In a first aspect, the present application provides a lithium ion battery silicon-carbon negative electrode slurry homogenizing process, which comprises the following steps: The artificial graphite, silicon-carbon, conductive carbon black and sodium carboxymethyl cellulose are mixed uniformly in proportion to obtain a mixture one; After the mixture one is preliminarily mixed with the single-walled carbon nanotube conductive slurry, part of water, polyacrylic acid binder, a molten carbonate compound, the remaining water and rubber are sequentially added thereto and are uniformly mixed. The part of water is added to make the solid content 60-65%. After each kind of substance is uniformly mixed, the next kind of substance is added, and the mixing temperature is not higher than 40 DEG C.
[0006] In a second aspect, the present application provides a lithium ion battery silicon-carbon negative electrode slurry, which is prepared by the homogenizing process.
[0007] The beneficial effects achieved by one or more embodiments of the present application are as follows: The application further solves the problems of the air bubbles and the poor consistency of the surface density of the coated pole piece caused by the gas produced by the slurry itself and the sharp increase of the viscosity of the slurry by adding part of water to control the solid content at 64-65%, and by controlling the temperature of the slurry to be less than 40 DEG C during stirring, and by adding the single-walled carbon nanotube conductive slurry and the polyacrylic acid binder in stages. BRIEF DESCRIPTION OF DRAWINGS
[0008] The accompanying drawings, which form a part of this specification, are included to provide a further understanding of the application and are incorporated in and constitute a part of this specification. The embodiments of the present application, and their
[0009] Figure 1 Fig. 1 is a schematic diagram of the homogenization process of the slurry of the silicon-carbon negative electrode of the lithium ion battery provided by the application; Figure 2 Fig. 2 is a comparison of the static state of the slurry prepared in Example 1 (A), the slurry prepared in Comparative Example 1 (B), the slurry prepared in Example 2 (C) and the slurry prepared in Comparative Example 2 (D) after 48 hours; Figure 3 Fig. 3 is a SEM image of the pole piece prepared in the examples and the comparative examples, wherein A is the pole piece prepared in Example 1, B is the pole piece prepared in Example 2, C is the pole piece prepared in Example 3, and D is the pole piece prepared in Example 4. DETAILED DESCRIPTION
[0010] It should be noted that the following detailed description is illustrative only and is intended to provide further description of the application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0011] As described in the background, in the prior art, the negative electrode slurry will produce a large amount of air bubbles during long-term static or slow stirring, resulting in surface defects of the coated pole piece, and the pole piece cannot be used normally. At the same time, the viscosity of the slurry will increase sharply, affecting the consistency of the coating surface density.
[0012] In the initial dispersion and stirring stage of the preparation of the slurry, a large amount of air will be entrained into the slurry by high-speed mechanical stirring; the silicon-carbon negative electrode material, especially the nano-silicon material, has a high specific surface area and porosity, and the air pre-adsorbed in these pores will be released into the slurry during stirring; under certain conditions, some components in the slurry (such as the acidic groups of PAA and some impurities) may have weak chemical reactions, producing trace amounts of gas.
[0013] If the bubbles can escape quickly, there is no problem. However, the viscosity of the silicon-carbon negative electrode slurry is high, and the higher the viscosity of the slurry, the slower the speed of the bubble floating. PAA (polyacrylic acid) and CMC (sodium carboxymethyl cellulose) are both high molecular polymers. After they are dissolved in water, they can greatly increase the viscoelasticity of the slurry. When the bubbles are wrapped in such viscoelastic liquid, the liquid film is not easy to break, resulting in good bubble stability.
[0014] SBR (styrene-butadiene rubber) is a latex particle, which also contains surfactants to maintain its emulsion stability. These surfactants can significantly reduce the surface tension of the slurry, although they are beneficial to wetting the particles, but at the same time, they also make the bubbles more easily generated and stable.
[0015] Conductive agents (such as SP, carbon nanotubes) and nano-silicon materials are all ultra-fine particles, which have lipophilic or hydrophilic properties. These particles can be adsorbed on the gas-liquid interface, physically hindering the coalescence and collapse of the bubbles.
[0016] The above is the reason for the existence of a large number of bubbles in the silicon-carbon negative electrode slurry. When there are a large number of bubbles in the negative electrode slurry, the bubbles will be retained on the surface of the electrode sheet during the coating process. During the drying process, the bubbles break or fail to completely discharge, forming pits or surface defects, resulting in inconsistent coating surface density, affecting the processing quality of the electrode sheet, and further affecting the performance of the battery.
[0017] A large number of small and stable bubbles dispersed in the slurry increase the internal flow resistance of the slurry, resulting in a significant increase in apparent viscosity. The carboxyl group (-COOH) of PAA and the carboxylate group (-COO - ) of CMC can form a bridge through hydrogen bonding or metal ions, producing an unstable three-dimensional network structure. This network will wrap the active material and solvent, causing the slurry to change from a good flow state to a gel state, with a sharp increase in viscosity.
[0018] The stability of the SBR emulsion will decrease in an acidic environment (provided by PAA) and a high ionic strength environment (from CMC and conductive agents). Under long-term static or slow shear, SBR latex particles may undergo local demulsification and agglomeration, forming larger colloidal particles. These colloidal particles will destroy the uniformity of the slurry and enhance the three-dimensional network structure of the slurry, resulting in an increase in viscosity and sedimentation.
[0019] During the standing and slow stirring process, a small amount of water in the surface layer of the slurry will evaporate, causing the surface layer of the slurry to locally concentrate and increase in viscosity. During the standing process, the solvent (water) and polymer (PAA, CMC) in the slurry may undergo phase separation or redistribution. The long chains of the polymer will intertwine and stretch, further strengthening the network structure. This process is called thixotropy recovery or aging thickening.
[0020] Silicon-carbon materials have relatively low density but are prone to agglomeration, and conductive agents have even lower density. When left to stand, they can form loose flocs if there is not enough shear force to maintain their dispersion. These flocs encapsulate a large amount of solvent inside and interlock into a network, which can also cause the overall viscosity of the slurry to increase.
[0021] During the coating process, the slurry needs to be extruded through a slit and uniformly distributed on the surface of the current collector. If the viscosity is too high, the slurry is difficult to spread uniformly and is prone to local accumulation or uneven thickness, resulting in inconsistent coating surface density. The bubble stability of high-viscosity slurry is enhanced, and the bubbles are encapsulated in the slurry and are difficult to escape. During the coating process, these bubbles can form pits or hollow defects on the surface of the pole piece, directly destroying the consistency of the coating surface density. In addition, the uneven distribution of materials in the region caused by the rupture of bubbles can further exacerbate the fluctuation of coating quality.
[0022] To solve the above problems, the present application provides a uniform slurry process for a lithium ion battery silicon-carbon negative electrode slurry, comprising the following steps: Mix artificial graphite, silicon-carbon, conductive carbon black and sodium carboxymethyl cellulose in proportion to obtain a mixture I; After the mixture I is preliminarily mixed with the single-walled carbon nanotube conductive slurry, part of the water, the polyacrylic acid binder, the molten carbonate compound, the remaining water and the rubber are sequentially added thereto and mixed uniformly. The solid content is 60-65% after adding part of the water. After each addition of a substance is mixed uniformly, the next substance is added, and the mixing temperature is not higher than 40°C.
[0023] The solid content refers to the mass percentage of the non-volatile part (including powder, binder, additive, etc.) remaining after the slurry is dried under specified conditions, also known as "solid content". Its calculation formula is: solid content (%) = (dry solid mass / dry sample total mass) x 100%.
[0024] The inventors have found through experiments that if part of the water is added, the solid content in the slurry is higher than 65%, the viscosity of the slurry will increase significantly, increasing the friction between the materials, thereby causing high shear force. This high shear force can damage the carbon layer on the surface of the silicon-carbon particles, making it easier for water to penetrate into the silicon-carbon particles.
[0025] Silicon reacts with water to generate hydrogen gas, and this reaction is particularly significant at the nanoscale. The generated gas forms bubbles in the slurry, which are difficult to completely escape during the coating process, leaving pits or hollow defects on the surface of the pole piece.
[0026] High temperature of the slurry can accelerate the chemical reaction rate, especially the reaction between silicon and water. In addition, high temperature can also reduce the viscoelasticity of the slurry, making it more difficult for bubbles to escape.
[0027] In the homogenization process, the solid content and slurry temperature are strictly controlled to ensure that the solid content is between 60-65% and the mixing temperature does not exceed 40℃. This can effectively reduce the generation of bubbles and improve the stability of the slurry and the coating quality.
[0028] Single-walled carbon nanotube (SWCNT) conductive slurry and polyacrylic acid (PAA) both contain a large number of polar groups such as carboxyl (-COOH) and hydroxyl (-OH). These polar groups can easily form strong intermolecular hydrogen bonds in aqueous solution. When both are added at the same time, hydrogen bonds will quickly form in large quantities, leading to an increase in the degree of cross-linking inside the slurry. The widespread formation of hydrogen bonds can significantly increase the viscoelasticity of the slurry, causing the slurry to change from a state of good flowability to a gel-like or even solid state. This sharp increase in viscosity not only makes it difficult for subsequent materials to disperse uniformly, but also makes it difficult for bubbles to escape during the coating process, thereby affecting the surface quality and consistency of the surface density of the pole piece.
[0029] In the homogenization process, if single-walled carbon nanotube conductive slurry is directly mixed with polyacrylic acid, the viscosity of the slurry will increase exponentially in a short time, making it difficult for the stirring equipment to effectively disperse the material, which may cause local high shear force, damage the surface structure of the silicon-carbon particles, and further exacerbate water penetration and gas generation.
[0030] In the present application, the single-walled carbon nanotubes are dispersed first, and then the polyacrylic acid glue solution is added. Before the addition of polyacrylic acid, the single-walled carbon nanotube conductive slurry has been fully dispersed and forms a stable pre-mixed system with water. At this time, the polar groups on the surface of the single-walled carbon nanotubes are mainly combined with water molecules, reducing the possibility of forming hydrogen bonds with other substances (such as polyacrylic acid). The dispersed single-walled carbon nanotubes can better mix with other ingredients, avoiding the formation of local high-viscosity regions due to uneven dispersion.
[0031] When polyacrylic acid is added alone, due to its low concentration, the hydrogen bond network formed is relatively sparse and does not immediately significantly increase the overall viscosity of the slurry. When polyacrylic acid is mixed with the dispersed single-walled carbon nanotubes, its hydrogen bond effect is gradually introduced rather than concentrated instantaneously. This can prevent the slurry from prematurely entering a high-viscosity state, ensuring the smooth progress of subsequent process operations.
[0032] After the mixture is initially mixed with the single-walled carbon nanotube conductive slurry, a portion of water is first added to control the solid content to be between 60-65%. This solid content range can effectively reduce the generation of bubbles and prevent the slurry from having too high a viscosity.
[0033] Fused carbonate compounds (such as ethylene carbonate) have a low melting point and are usually added after being heated to a liquid state. Such compounds can play a certain role in wetting and dispersing in the slurry, while avoiding the problem of local high viscosity that may be caused by directly adding solids. In addition, the carbonate compound in a molten state is easier to mix uniformly with other ingredients in the slurry, thereby improving the overall stability of the slurry.
[0034] After adding the remaining water, further uniform distribution of the components in the slurry can be ensured by long-time high dispersion through gradually increasing the dispersion speed. This dispersion method helps to eliminate local high viscosity areas, while avoiding the problem of too fast dilution of the slurry caused by adding too much water at once, which affects the final performance (the stability of the slurry depends on the three-dimensional network structure formed inside it, which is formed by polymer chains (such as PAA and CMC) bridged by hydrogen bonds or metal ions. If too much water is added at once, the interaction between polymer chains will be weakened, thereby destroying the original network structure. This destruction will cause the slurry to change from a relatively stable gel state to an excessively diluted state, further exacerbating the generation and stability of bubbles).
[0035] Rubber (such as styrene butadiene rubber, SBR) contains surfactants in itself as emulsion particles to maintain its emulsion stability. If the rubber is added too early, it may cause local demulsification or agglomeration due to high shear force, affecting the uniformity of the slurry. Therefore, adding the rubber after all other ingredients are fully dispersed can minimize the mechanical stress it is subjected to, thereby maintaining the stability of the slurry.
[0036] In some embodiments, the mass ratio of graphite, silicon-carbon, conductive carbon black, sodium carboxymethyl cellulose, single-walled carbon nanotubes, polyacrylic acid, ethylene carbonate, and rubber is 65-82:10-20:0.7-1.2:0.2-0.5:0.05-0.3:1.5-2.5:1.0-2.0:0.4-0.6.
[0037] The above mass ratio refers to the mass ratio of the powder of the raw material.
[0038] Preferably, the solid content in the single-walled carbon nanotube conductive slurry is 1.0%-4.0%; or, the solid content in the polyacrylic acid binder is 4-7%; or, the solid content in the rubber is 40-50%.
[0039] Preferably, the rubber is styrene butadiene rubber.
[0040] In some embodiments, the addition of part of the water makes the solid content 64-65%.
[0041] In some embodiments, the mixing speed of the mixture I and the single-walled carbon nanotube conductive paste is 15-25 rpm, and the mixing time is 10-30 min. The main purpose is to ensure that the material can be fully wetted and preliminarily dispersed, while avoiding damage to the surface structure of the silicon-carbon particles due to excessive shear force. Lower stirring speed helps to reduce mechanical stress and prevent problems caused by local high shear force, such as water penetrating into the silicon-carbon particles to trigger chemical reactions (such as the reaction of silicon and water to generate hydrogen) and the generation of bubbles. In addition, under low-speed stirring, the single-walled carbon nanotubes can be better mixed with other ingredients, avoiding local high-viscosity areas caused by uneven dispersion. If the stirring speed is too high, it may cause a large amount of air to be entrained in the paste, increasing the risk of bubble generation and possibly causing the paste temperature to rise, accelerating the rate of unwanted chemical reactions.
[0042] In some embodiments, after adding part of the water, first stir at a stirring speed of 15-25 rpm for 10-30 min; then mix at a stirring speed of 15-25 rpm and a dispersion speed of 400-600 rpm for 20-40 min; finally, adjust the dispersion speed to 800-1000 rpm and continue to disperse for 30-60 min.
[0043] Low-speed stirring is to ensure that the added part of the water can fully wet the solid particles in the mixture I, avoiding high shear force or agglomeration caused by uneven distribution of local moisture. At the same time, low-speed stirring can reduce mechanical stress and prevent water from penetrating into the silicon-carbon particles, thereby avoiding the chemical reaction of silicon and water to generate hydrogen. In addition, low-speed stirring can also reduce the risk of air being entrained in the paste and the possibility of bubble generation.
[0044] After the preliminary wetting is completed, the dispersion speed is increased to 400-600 rpm, which helps to further break the agglomeration between the solid particles and promote the uniform dispersion of the conductive agent such as single-walled carbon nanotubes. The moderate dispersion speed in this stage can ensure the uniformity of the paste while avoiding damage to the carbon layer on the surface of the silicon-carbon particles or triggering unnecessary chemical reactions due to excessive shear force. In addition, moderate dispersion also helps to preliminarily form a three-dimensional network structure of the paste, laying the foundation for subsequent control of high-viscosity state.
[0045] Finally, adjust to a high dispersion speed (800-1000 rpm) to further refine the particle distribution in the paste and ensure uniform mixing of all components. The high dispersion speed in this stage can effectively eliminate local high-viscosity areas and optimize the overall stability of the paste. At the same time, high dispersion speed also helps to expel the small bubbles remaining in the paste, improving the coating quality.
[0046] In some embodiments, after adding the polyacrylic acid binder, the dispersion is carried out at a stirring speed of 15-25 rpm and a dispersion speed of 1200-1500 rpm for 10-20 min.
[0047] When the polyacrylic acid binder is added, the slurry already contains single-walled carbon nanotubes and part of the water, and the solid content is high (60-65%). The polyacrylic acid is easy to form a network structure through hydrogen bonds, and a low dispersion speed (1200-1500 rpm) can avoid excessive local shear force leading to gelation, while ensuring uniform coating of the particles by the binder.
[0048] In some embodiments, after adding the molten carbonate compound, the dispersion is carried out at a stirring speed of 20-25 rpm and a dispersion speed of 1500-1650 rpm for 10-20 min.
[0049] The carbonate compound is ethylene carbonate or propylene carbonate.
[0050] After adding the molten carbonate compound, it can reduce the internal friction of the slurry as a low-viscosity additive. At this time, increasing the dispersion speed (1500-1650 rpm) can promote the interfacial wetting of the carbonate with the active material and the conductive agent, and enhance the dispersion uniformity.
[0051] In some embodiments, after adding the remaining water, the dispersion is carried out at a stirring speed of 20-25 rpm and a dispersion speed of 1650-1800 rpm for 120-150 min.
[0052] After adding the remaining water, the solid content of the slurry is reduced, and the system fluidity is improved. Higher dispersion speed (1650-1800 rpm) combined with long-time dispersion (120-150 min) can further break the particle agglomeration, ensure uniform distribution of water, avoid local concentration differences leading to viscosity fluctuations, and ultimately achieve high uniformity and stability of the slurry.
[0053] In some embodiments, after adding the rubber, the dispersion is carried out at a stirring speed of 15-25 rpm and a dispersion speed of 200-400 rpm for 30-60 min. The dispersion speed is relatively low after adding the rubber (such as styrene-butadiene rubber SBR), mainly because the stability of the rubber depends on the surfactant to maintain the emulsion state. If the dispersion speed is too high, local high shear force will be generated, leading to emulsion breaking and particle agglomeration, which will destroy the uniformity of the slurry. At this time, the slurry system has formed a stable structure through previous high dispersion, and a low dispersion speed (200-400 rpm) can avoid mechanical stress from damaging the network structure, while ensuring uniform dispersion of the rubber particles without agglomeration, ultimately ensuring the stability and coating performance of the slurry.
[0054] In a second aspect, the present application provides a lithium ion battery silicon-carbon negative electrode slurry prepared by the uniform slurry process.
[0055] The application will be further described in conjunction with specific embodiments.
[0056] Example 1 The homogenizing process of the silicon-carbon negative electrode slurry of lithium ion battery, as shown in the figure, includes the following steps: Figure 1 Step 1, mix graphite 72.25 kg, silicon-carbon 12.75 kg, conductive carbon black 0.823 kg, and sodium carboxymethyl cellulose 0.265 kg powders, stirring speed 25 rpm (forward rotation), dispersion speed 400 rpm for 15 min powder mixing. Step 2, add single-walled carbon nanotube conductive slurry (solid content 1%) 15.48 kg to the powder in step 1 for mixing, stirring speed 15 rpm (reverse rotation) for 15 min preliminary wetting, to obtain slurry 1; then add deionized water 30 kg to slurry 1, stirring for 10 min, stirring speed 10 rpm (forward rotation), so that the solid content reaches 65%.
[0057] Step 3, further soak the slurry after preliminary wetting in step 2, mix according to stirring speed 25 rpm (forward rotation), dispersion speed 400 rpm for 30 min, simultaneously enable circulating chilled water during the process to make the slurry temperature below 40℃; then mix according to stirring speed 25 rpm (forward rotation), dispersion speed 800 rpm for 60 min, simultaneously enable circulating chilled water during the process to make the slurry temperature below 40℃, to obtain slurry 2.
[0058] Step 4, add polyacrylic acid binder (solid content 6%) 30.957 kg to slurry 2, high-speed dispersion according to stirring speed 25 rpm (forward rotation), dispersion speed 1200 rpm for 10 min, simultaneously enable circulating chilled water during the process to make the slurry temperature below 40℃, to obtain slurry 3.
[0059] Step 5, add ethylene carbonate 1.7 kg which becomes liquid after heating at 50℃ to slurry 3, high-speed dispersion according to stirring speed 25 rpm (forward rotation), dispersion speed 1500 rpm for 10 min, simultaneously enable circulating chilled water during the process to make the slurry temperature below 40℃, to obtain slurry 4.
[0060] Step 6, add deionized water 19.033 kg to slurry 4, high-speed dispersion according to stirring speed 25 rpm (forward rotation), dispersion speed 1650 rpm for 120 min, simultaneously enable circulating chilled water during the process to make the slurry temperature below 40℃, vacuum degree ≤-80 kpa, to obtain slurry 5.
[0061] Step 6, add deionized water 19.033 kg to slurry 4, high-speed dispersion according to stirring speed 25 rpm (forward rotation), dispersion speed 1650 rpm for 120 min, simultaneously enable circulating chilled water during the process to make the slurry temperature below 40℃, vacuum degree ≤-80 kpa, to obtain slurry 5.
[0062] Step 7, add styrene butadiene rubber (solid content 40%) 1.106 kg into slurry 5, disperse for 30 min at stirring speed 25 rpm (forward rotation) and dispersion speed 400 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 40℃ and vacuum degree ≤-80 kpa, to obtain finished slurry.
[0063] Example 2 The homogenizing process of the lithium ion battery silicon-carbon negative electrode slurry comprises the following steps: Step 1, mix graphite 68 kg, silicon-carbon 17 kg, conductive carbon black 0.89 kg, and carboxymethyl cellulose sodium 0.356 kg powders, and mix for 15 min at stirring speed 25 rpm (forward rotation) and dispersion speed 400 rpm.
[0064] Step 2, add single-walled carbon nanotube conductive slurry (solid content 1%) 22.25 kg into the powders in step 1 to mix, and preliminarily wet for 15 min at stirring speed 15 rpm (reverse rotation) to obtain slurry 1; then add deionized water 24.5 kg to stir for 10 min at stirring speed 10 rpm (forward rotation) to make the solid content reach 65%.
[0065] Step 3, further wet the slurry preliminarily wetted in step 2, and mix for 30 min at stirring speed 25 rpm (forward rotation) and dispersion speed 400 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 40℃; then mix for 60 min at stirring speed 25 rpm (forward rotation) and dispersion speed 800 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 40℃, to obtain slurry 2.
[0066] Step 4, add polyacrylic acid binder (solid content 6%) 37.086 kg into slurry 2, and high-speed disperse for 10 min at stirring speed 25 rpm (forward rotation) and dispersion speed 1200 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 40℃, to obtain slurry 3.
[0067] Step 5, add ethylene carbonate 1.7 kg heated to become liquid at 50℃ into slurry 3, and high-speed disperse for 10 min at stirring speed 25 rpm (forward rotation) and dispersion speed 1500 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 40℃, to obtain slurry 4.
[0068] Step 6, add deionized water 20.728 kg into slurry 4, and high-speed disperse for 120 min at stirring speed 25 rpm (forward rotation) and dispersion speed 1650 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 40℃ and vacuum degree ≤-80 kpa, to obtain slurry 5.
[0069] Step 7, add styrene butadiene rubber (solid content 40%) 1.113 kg to slurry 5, disperse at stirring speed 25 rpm (forward rotation) and dispersion speed 400 rpm for 30 min, and simultaneously start circulating chilled water to keep the slurry temperature below 40°C and vacuum degree ≤-80 kpa, to obtain the finished slurry.
[0070] Example 3 The homogenizing process of the lithium ion battery silicon-carbon negative electrode slurry comprises the following steps: Step 1, mix graphite 65 kg, silicon-carbon 15 kg, conductive carbon black 0.84 kg, and carboxymethyl cellulose sodium 0.31 kg powders, stir at stirring speed 25 rpm (forward rotation) and dispersion speed 400 rpm for 15 min to mix the powders.
[0071] Step 2, add single-walled carbon nanotube conductive slurry (solid content 1%) 20.13 kg to the powders in step 1 to mix, stir at stirring speed 20 rpm (reverse rotation) for 20 min to preliminarily wet, to obtain slurry 1; then add deionized water to stir for 10 min at stirring speed 10 rpm (forward rotation) to make the solid content reach 64%.
[0072] Step 3, further wet the slurry preliminarily wetted in step 2, mix at stirring speed 20 rpm (forward rotation) and dispersion speed 500 rpm for 30 min, and simultaneously start circulating chilled water to keep the slurry temperature below 40°C; then mix at stirring speed 25 rpm (forward rotation) and dispersion speed 900 rpm for 50 min, and simultaneously start circulating chilled water to keep the slurry temperature below 40°C, to obtain slurry 2.
[0073] Step 4, add polyacrylic acid binder (solid content 6%) 34.023 kg to slurry 2, high-speed disperse at stirring speed 25 rpm (forward rotation) and dispersion speed 1400 rpm for 10 min, and simultaneously start circulating chilled water to keep the slurry temperature sbr below 40°C, to obtain slurry 3.
[0074] Step 5, add ethylene carbonate 1.5 kg heated to become liquid at 50°C to slurry 3, high-speed disperse at stirring speed 20 rpm (forward rotation) and dispersion speed 1550 rpm for 10 min, and simultaneously start circulating chilled water to keep the slurry temperature below 40°C, to obtain slurry 4.
[0075] Step 6, add 20.715 kg of deionized water to slurry 4, and perform high-speed dispersion at a stirring speed of 25 rpm (forward rotation) and a dispersion speed of 1750 rpm for 130 min, while synchronously starting the circulation of chilled water to keep the slurry temperature below 40°C and the vacuum degree less than or equal to -80 kPa, to obtain slurry 5.
[0076] Step 7, add 1.133 kg of butadiene-styrene rubber (solid content of 40%) to slurry 5, and perform dispersion at a stirring speed of 20 rpm (forward rotation) and a dispersion speed of 300 rpm for 40 min, while synchronously starting the circulation of chilled water to keep the slurry temperature below 40°C and the vacuum degree less than or equal to -80 kPa, to obtain the finished slurry.
[0077] Comparative Example 1 Compared with Example 1, the material composition is the same, but the homogenization process is different.
[0078] The lithium ion silicon-carbon negative electrode homogenization process specifically includes the following steps: Step 1, mix 0.265 kg of sodium carboxymethyl cellulose and 21.818 kg of deionized water at a stirring speed of 35 rpm and a dispersion speed of 1500 rpm for 180 min dispersion to obtain a sodium carboxymethyl cellulose glue solution.
[0079] Step 2, mix 0.823 kg of conductive carbon black, 15.48 kg of single-walled carbon nanotube conductive slurry, 30.957 kg of polyacrylic acid glue solution, and 1.6 kg of deionized water into 22.083 kg of the sodium carboxymethyl cellulose glue solution, and perform 5 min of pre-dispersion at a stirring speed of 15 rpm and a dispersion speed of 300 rpm, and then perform 90 min of high-speed dispersion at a stirring speed of 20 rpm and a dispersion speed of 1800 rpm to obtain slurry 1.
[0080] Step 3, add 12.75 kg of silicon-carbon and 72.25 kg of graphite powder to slurry 1, and perform 10 min of pre-dispersion at a stirring speed of 15 rpm and a dispersion speed of 300 rpm, and then continue high-speed dispersion at a stirring speed of 20 rpm and a dispersion speed of 1800 rpm for 150 min, while synchronously starting the circulation of chilled water to keep the slurry temperature at 40°C and the vacuum degree less than or equal to -80 kPa, to obtain slurry 2.
[0081] Step 4, add 42.367 kg of deionized water to slurry 2, and continue high-speed dispersion at a stirring speed of 25 rpm and a dispersion speed of 1500 rpm for 150 min, while synchronously starting the circulation of chilled water to keep the slurry temperature at 40°C and the vacuum degree less than or equal to -80 kPa, to obtain slurry 3.
[0082] Step 5, add 1.106 kg of styrene-butadiene rubber to slurry 3, continue to disperse for 30 min at stirring speed of 25 rpm and dispersing speed of 200 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 45 DEG C and vacuum degree less than or equal to -80 kPa, to obtain finished slurry.
[0083] Comparative Example 2 Compared with Example 1, the material composition is the same, and the homogenizing process is different.
[0084] The lithium ion silicon-carbon negative electrode homogenizing process specifically includes the following steps: Step 1, mix 0.356 kg of sodium carboxymethyl cellulose and 29.311 kg of deionized water at stirring speed of 35 rpm and dispersing speed of 1500 rpm for 180 min to obtain sodium carboxymethyl cellulose glue solution.
[0085] Step 2, mix 0.89 kg of conductive carbon black, 22.25 kg of single-walled carbon nanotube conductive slurry, 37.086 kg of polyacrylic acid glue solution, 1.6 kg of deionized water, and 29.667 kg of sodium carboxymethyl cellulose glue solution, and pre-disperse for 5 min at stirring speed of 15 rpm and dispersing speed of 300 rpm, and then high-speed disperse for 90 min at stirring speed of 20 rpm and dispersing speed of 1800 rpm to obtain slurry 1.
[0086] Step 3, add 17 kg of silicon-carbon and 68 kg of graphite powder to slurry 1, pre-disperse for 10 min at stirring speed of 15 rpm and dispersing speed of 300 rpm, and then continue to high-speed disperse for 150 min at stirring speed of 20 rpm and dispersing speed of 1800 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature 40 DEG C and vacuum degree less than or equal to -80 kPa, to obtain slurry 2.
[0087] Step 4, add 27.816 kg of deionized water to slurry 2, and continue to high-speed disperse for 150 min at stirring speed of 25 rpm and dispersing speed of 1500 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 45 DEG C and vacuum degree less than or equal to -80 kPa, to obtain slurry 3.
[0088] Step 5, add 1.113 kg of styrene-butadiene rubber to slurry 3, continue to disperse for 30 min at stirring speed of 25 rpm and dispersing speed of 200 rpm, and simultaneously start circulating refrigerated water to make the slurry temperature below 45 DEG C and vacuum degree less than or equal to -80 kPa, to obtain finished slurry.
[0089] Comparative Example 3 The difference from example 1 is that in the homogenization process, single-walled carbon nanotube conductive paste and polyacrylic acid binder are added at the same time in step 2, and dispersion is carried out synchronously, and the others are the same as example 1.
[0090] The slurries prepared in the examples and comparative examples were respectively tested for viscosity, solid content, long-term standing gas production, and electrode SEM using a Brookfield DV2T series viscometer, a solid content tester, a scanning electron microscope-energy spectrometer, and other related equipment.
[0091] Table 1 test data of slurry solid content and viscosity of examples and comparative examples
[0092] Table 2 comparison of long-term standing viscosity stability of examples and comparative examples
[0093] From Figure 2 As shown in Table 2, the negative electrode slurry prepared in the examples has excellent stability after standing for 72h, and the viscosity of the negative electrode slurry prepared in the comparative examples increases proportionally.
[0094] As shown in Table 2, the negative electrode slurry prepared in the examples has excellent stability after standing for 72h, and the viscosity of the negative electrode slurry prepared in the comparative examples increases proportionally.
[0095] The appearance of the electrode sheet and the coating surface density are obviously improved, as shown in Table 1.
[0096] The negative electrode slurry prepared in the examples has uniform dispersion without agglomeration when preparing the negative electrode sheet, as shown in A and C of Table 1. Figure 3 The negative electrode slurry prepared in the comparative examples has slight agglomeration in dispersion, as shown in B and D of Table 1. Figure 3 The negative electrode slurry prepared in the comparative examples has slight agglomeration in dispersion, as shown in B and D of Table 1.
[0097] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Those skilled in the art can make various modifications and changes to the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A homogenization process of a lithium-ion battery silicon-carbon anode slurry, characterized in that: It comprises the following steps: Mixing artificial graphite, silicon carbon, conductive carbon black and sodium carboxymethyl cellulose in proportion to obtain mixture one; After mixing mixture one with single-walled carbon nanotube conductive slurry, add part of water, polyacrylic acid binder, melt carbonate compound, the rest of water and rubber in sequence and mix well; add part of water to make the solid content 60-65%; after mixing well after adding one kind of material, add the next kind of material, and the mixing temperature is not higher than 40℃.
2. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: The mass ratio of graphite, silicon carbon, conductive carbon black, sodium carboxymethyl cellulose, single-walled carbon nanotube, polyacrylic acid, vinyl carbonate and rubber is 65-82:10-20:0.7-1.2:0.2-0.5:0.05-0.3:1.5-2.5:1.0-2.0:0.4-0.6; Preferably, the solid content of single-walled carbon nanotube conductive slurry is 1.0%-4.0%; Or, the solid content of polyacrylic acid binder is 4-7%; Or, the solid content of rubber is 40-50%; Preferably, the rubber is styrene-butadiene rubber.
3. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: Add part of water to make the solid content 64-65%.
4. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: The mixing and stirring speed of mixture one and single-walled carbon nanotube conductive slurry is 15-25rpm, and the mixing time is 10-30min.
5. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: After adding part of water, first stir and mix at stirring speed 15-25rpm for 10-30min; then mix at stirring speed 15-25rpm and dispersion speed 400-600rpm for 20-40min; finally, adjust the dispersion speed to 800-1000rpm and continue to disperse for 30-60min.
6. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: After adding polyacrylic acid binder, disperse at stirring speed 15-25rpm and dispersion speed 1200-1500rpm for 10-20min.
7. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: After adding melt carbonate compound, disperse at stirring speed 20-25rpm and dispersion speed 1500-1650rpm for 10-20min.
8. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: After adding the rest of water, highly disperse at stirring speed 20-25rpm and dispersion speed 1650-1800rpm for 120-150min.
9. The process for homogenization of lithium ion battery silicon-carbon anode slurry as claimed in claim 1 wherein: After adding rubber, disperse at stirring speed 15-25rpm and dispersion speed 200-400rpm for 30-60min.
10. A lithium ion battery silicon-carbon anode slurry, characterized in that: Prepared by the homogenate process of any one of claims 1-9. Prepared by the homogenate process of any one of claims 1-9.
Citation Information
Cited By
Negative electrode binder, slurry, lithium-ion battery and its preparation method
CN122563503A